2022
DOI: 10.3390/plants11223045
|View full text |Cite
|
Sign up to set email alerts
|

Relative Water Content, Proline, and Antioxidant Enzymes in Leaves of Long Shelf-Life Tomatoes under Drought Stress and Rewatering

Abstract: Some physiological, oxidative, and antioxidant enzymatic patterns were assessed in plants of three local Sicilian landraces of long shelf-life tomatoes (‘Custonaci’, ‘Salina’, and ‘Vulcano’), as compared to the commercial tomato hybrid ‘Faino’ (control). Three water treatments were considered in open-field: DRY (no irrigation); IRR (long-season full irrigation); REW (drought/rewatering cycles). During the growing season, soil water deficit (SWD) was estimated, and relative water content (RWC), specific leaf ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Consequently, while it is essential to disaggregate the effects of drought and high temperature on plant productivity, the interactions between these two stressors will complicate this effort. The observed multi-trait effect from drought and heat stress points to a broad spectrum and, possibly, the catastrophic impact of these stresses on plant performance [ 105 ]. These stress factors denature protein constituents of the cell membrane and make structures more prone to rupture, often increasing membrane fluidity and ion leakage.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Consequently, while it is essential to disaggregate the effects of drought and high temperature on plant productivity, the interactions between these two stressors will complicate this effort. The observed multi-trait effect from drought and heat stress points to a broad spectrum and, possibly, the catastrophic impact of these stresses on plant performance [ 105 ]. These stress factors denature protein constituents of the cell membrane and make structures more prone to rupture, often increasing membrane fluidity and ion leakage.…”
Section: 0 Discussionmentioning
confidence: 99%
“…6 , is consistent with the observations of Khan et al (2015) , who reported a decrease in RWC to 89.28% in drought-treated plants compared to control variants. Moreover, RWC values above 75% indicate a normal plant water status even under exposure to drought stress ( Patanè et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proline accumulation was higher in drought tolerant plants than sensitive types, this was due to a higher water holding capacity in tolerant types. Other researchers also found that high proline counts in drought tolerant lines indicated high e ciency of the antioxidant system (Patanè et al 2022;Gao et al 2023).…”
Section: Introductionmentioning
confidence: 90%